The Influence of Facilities, Service Quality, and Price Perception on Customer Satisfaction at PT. Grab Indonesia - Faeni, Ratih; Puspaningtyas Faeni, Dewi; El Kafafi, Siham (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2025)
The influence of facilities, service quality, and price perception on customer satisfaction at PT. Grab Indonesia is a literature review article within the scope of economics and business. The purpose of this article is to formulate hypotheses regarding the relationships between variables that will be used in future research. The research object includes online literature from sources such as Google Scholar, Mendeley, and other academic online media. The research method involved 100 respondents using a Non- Probability Sampling technique with a purposive approach, employing quantitative descriptive analysis. The results of this article indicate that: 1) facilities do not have a significant impact on customer satisfaction; 2) service quality has a significant impact on customer satisfaction; and 3) price perception has a significant impact on customer satisfaction.